Thermoplastic polyurethane elastomer flexible composite solid electrolyte as well as preparation method and application thereof
By introducing etheroxy segments and inorganic fillers into the flexible composite solid electrolyte to form a crosslinking network, the problem of insufficient ion conductivity of the existing electrolyte is solved, and efficient ion transmission and cycling stability is achieved, which is suitable for wearable electronic devices.
Patent Information
- Application Number
- CN202411831335.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-28
AI Technical Summary
The existing flexible composite solid electrolytes have insufficient ion conductivity in lithium-ion batteries, making it difficult to meet the needs of wearable electronic devices.
Thermoplastic polyurethane elastomer flexible composite solid electrolyte is used to introduce etheroxy-based fragments and inorganic fillers that can bind to lithium ions into the polymer matrix to form a crosslinking network rich in etheroxy groups to improve ion transport efficiency.
It realizes high ionic conductivity and cyclic stability of composite solid electrolytes, and is suitable for wearable electronic devices.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium metal battery solid electrolytes, and in particular relates to a thermoplastic polyurethane elastomer flexible composite solid electrolyte and a preparation method and application thereof. Background Art
[0002] Driven by the rapid development of new energy storage solutions in the automotive industry, lithium-ion batteries are moving towards higher energy density, higher safety and longer service life. On the one hand, lithium-ion batteries using traditional liquid electrolytes still face serious safety hazards caused by electrolyte leakage and irreversible decomposition; on the other hand, the energy density of the existing high-nickel-content cathode / carbon-silicon anode system has reached ~300Wh kg -1 The current lithium-ion batteries cannot meet the needs of electric vehicles and other fields due to the limit of energy storage. Therefore, due to the pursuit of safety and high energy density, people are increasingly interested in solid-state lithium-ion batteries. In addition, solid-state lithium-ion batteries are easier to develop towards miniaturization and flexibility, so they are more suitable as energy storage devices for penetrable batteries, wearable electronic devices and flexible electronic devices.
[0003] Existing flexible and foldable solid electrolytes are mainly concentrated in gel semi-solid electrolytes, but they are limited by the low ionic conductivity of the gel electrolyte itself. At the same time, the gel material with poor mechanical properties is also difficult to resist the puncture of lithium dendrites generated during long-term cycles. In contrast, compared with gel semi-solid electrolytes, organic-inorganic composite solid electrolytes have sufficient mechanical strength to resist the puncture of lithium dendrites on the one hand, and the introduced inorganic fillers increase the transmission mode of ions in the electrolyte, enhancing the overall ion transmission performance of the electrolyte. Therefore, organic-inorganic composite solid electrolyte materials are regarded as one of the candidates for the next generation of solid-state battery electrolyte materials.
[0004] The patent document CN202410263514.X previously applied by our research group discloses a flexible composite solid electrolyte and its preparation method and application, wherein the flexible composite solid electrolyte is prepared from the following raw materials in weight percentage: solute salt 5wt%~30wt%; inorganic filler 5wt%~80wt%; polymer substrate 10wt%~80wt%, the polymer substrate is composed of polymer A and compound B in a mass ratio of 1~10:1, polymer A is one or more of polyether polyurethane or polyester polyurethane, and compound B is one or more of fluorine-containing polymers ethylene-tetrafluoroethylene copolymer, polytetrafluoroethylene, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylenechlorotrifluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride or polyvinylidene fluoride-hexafluoropropylene; the flexible composite solid electrolyte has a high voltage window of 5.0V, which can fully match the high-voltage positive electrode material, and the assembled lithium iron phosphate / nickel cobalt manganese battery can achieve stable circulation while having a high specific capacity. However, the ionic conductivity of lithium metal batteries assembled based on this flexible composite solid electrolyte still needs to be further improved to better meet the use of wearable electronic devices. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a thermoplastic polyurethane elastomer flexible composite solid electrolyte and a preparation method thereof. The composite solid electrolyte prepared by the method has excellent mechanical properties. A symmetrical lithium battery assembled based on the composite solid electrolyte can achieve stable circulation. In addition, the prepared composite solid electrolyte also has high flexibility and high ionic conductivity, making it possible to be applied to wearable electronic devices.
[0006] The present invention adopts the following technical solution to solve the above technical problems: a thermoplastic polyurethane elastomer flexible composite solid electrolyte, which is prepared from the following raw materials in weight percentage: 1 wt% to 30 wt% of a solute salt, wherein the solute salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluoroborate (LiPF6), lithium difluorooxalatoborate (LiDFOB), lithium nitrate (LiNO3) or lithium tetrafluoroborate (LiBF4); 5wt% to 50wt% of an inorganic filler, wherein the inorganic filler is one or more of an active filler or an inert filler, the active filler is one or more of a garnet filler, a perovskite material, a LISICON filler or a NASICON filler, and the inert filler is one or more of natural clay, SiO2 or Al2O3; 40wt% to 90wt% of a polymer matrix, the polymer matrix being composed of a polymer A and a compound B in a mass ratio of 1:1 to 20, wherein the polymer A is one or more of polyether polyurethane, polyester polyurethane, polyimide polyurethane or polyurea polyurethane, and the compound B is one or more of polyethylene glycol diacrylate (PEGDA), pentaerythritol triacrylate (PPETA) or pentaerythritol tetraacrylate (PETA); In the technical scheme of the present invention, polymer A and compound B respectively have ether radical fragments that can bind to lithium ions, so that lithium ions can be transmitted along the polymer chain segments. After ultraviolet treatment, compound B can self-crosslink in the polymer matrix to generate a cross-linked network rich in ether radicals, thereby promoting the transmission of lithium ions in the polymer matrix; inorganic fillers can also play the role of conducting ions, increase the ion transmission pathway in the composite solid electrolyte, and improve the ion transmission efficiency. Therefore, the thermoplastic polyurethane elastomer flexible composite solid electrolyte has a relatively high ion conductivity and ion migration number at room temperature; polymer A usually has excellent mechanical properties, and the hard segment and soft segment constituting polymer A can provide mechanical properties and ion conduction properties, respectively. Therefore, using polymer A as a polymer matrix can prepare a flexible composite solid electrolyte with excellent mechanical properties; compound B can be stimulated by external conditions (such as heating or ultraviolet treatment) to break double bonds and undergo free radical polymerization to generate a polymer cross-linked network rich in ether radicals, which can further enhance the ion transmission efficiency inside the polymer matrix. In addition, the synergistic effect between the polymer matrix and the inorganic filler after enhanced ion transmission further promotes the ion transmission performance of the composite solid electrolyte.
[0007] Preferably, the thermoplastic polyurethane elastomer flexible composite solid electrolyte is prepared from the following raw materials in the following weight percentage ratio: 20wt%~30wt% of solute salt, 5wt%~35wt% of inorganic filler, and the balance is polymer matrix.
[0008] Preferably, the garnet filler is Li 6.5 Ln3Z 1.4 Ta 0.5 O 12 or Li 7-x Ln3Z 2-x (Nb+Ta) x O 12 One or more of; the perovskite filler is Li 3x La 2 / 3-x TiO3 (LLTO); NASICON type filler is Li 1+x AlxTi 2-x (PO4)3 (LATP) or Li 1+x Al x Ge2-x (PO4)3(LAGP) or more.
[0009] Preferably, the mass ratio of polymer A to compound B in the polymer matrix is 1:2-5.
[0010] A method for preparing a thermoplastic polyurethane elastomer flexible composite solid electrolyte, the specific steps of which are: Step S1: dispersing polymer A in solvent C and heating and stirring until dissolved to obtain a precursor solution; Step S2: adding compound B to the precursor solution obtained in step S1 and stirring to mix evenly; Step S3: placing the mixed solution obtained in step S3 under an ultraviolet lamp for 30 to 120 minutes; Step S4: adding a solute salt to the mixed solution obtained in step S4 and stirring to mix uniformly; Step S5: uniformly dispersing the inorganic filler in the solvent C to obtain a suspension; Step S6: Add the suspension obtained in step S5 to the mixed solution obtained in step S4 and stir to mix evenly to obtain a solid electrolyte mixed solution, then evenly apply the solid electrolyte mixed solution on the mold, immerse it in solvent D to form it, take it out after immersion and vacuum dry it to obtain a thermoplastic polyurethane elastomer flexible composite solid electrolyte, which has good compatibility with lithium metal and also has excellent ion transmission ability.
[0011] Preferably, the solvent C in step S1 and step S5 is one or more of ethylene glycol dimethyl ether, N-methylpyrrolidone, dimethyl sulfoxide or N,N-dimethylformamide; the solvent D in step S6 is one or more of anhydrous ethanol or acetone.
[0012] Preferably, in step S3, the power of the ultraviolet lamp is 20W, and the wavelength of the emitted ultraviolet light is 365nm.
[0013] In the technical solution of the present invention, ultraviolet polymerization is used to complete the preparation of a thermoplastic polyurethane elastomer flexible composite solid electrolyte, wherein compound B can effectively undergo chemical transformation and energy transfer after absorbing light energy of ultraviolet rays of a specific wavelength (such as 365nm), thereby breaking the double bonds at both ends, thereby generating primary free radicals that can initiate polymerization, and these free radicals subsequently initiate a cross-linking reaction between compounds B to form a polymer cross-linked network with excellent ion conductivity.
[0014] Preferably, the stirring and mixing in step S1, step S2, step S4 and step S6 are all performed on a magnetic heating stirrer, and the heating and stirring temperature in step S1 is 60-90°C.
[0015] A lithium metal battery is assembled into a button cell using the above-mentioned flexible composite solid electrolyte, a lithium iron phosphate or nickel cobalt manganese 811 positive electrode and a lithium metal negative electrode.
[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects: The thermoplastic polyurethane elastomer flexible composite solid electrolyte prepared by the present invention has excellent mechanical properties. While ensuring that it can effectively resist the piercing of lithium dendrites to improve battery safety, it can also effectively improve the interface contact between the composite solid electrolyte and the lithium metal electrode, reduce the interface transmission impedance, and improve the efficiency of lithium ion transmission at the interface. On the basis of ensuring the mechanical properties, the introduction of the photo-initiated polymer ion-conducting network increases the number of ether oxygen groups available for lithium ion binding, increases the number of lithium ion binding sites in the polymer matrix of the composite solid electrolyte, and effectively improves the transmission efficiency of lithium ions along the polymer part in the composite solid electrolyte; the composite solid lithium metal battery prepared by the present invention has excellent ionic conductivity and cycle stability because it contains the flexible composite solid electrolyte with the above excellent properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The stress-strain curves of the composite solid electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2.
[0018] Figure 2 The electrochemical impedance diagrams of the composite solid electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0019] Figure 3 The composite solid electrolyte prepared in Example 1 and Comparative Example 1 is applied to a Li||Li symmetric battery at 0.1 mA / cm 2 Comparison of charge and discharge cycles under different current densities.
[0020] Figure 4 2C cycle comparison of the composite solid electrolyte prepared in Example 1 and Comparative Example 1 applied in LFP||Li battery.
[0021] Figure 5 The composite solid electrolyte prepared in Example 1 is applied to the NCM811||Li battery system at 0.2C charge and discharge curve. DETAILED DESCRIPTION
[0022] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1
[0023] Step S1: Weigh 2.0 g of polyether polyurethane (PEUR, Yantai Wanhua WHT-8190RV) and 8 mL The mixture was mixed with DMF solvent and stirred at 80°C and 600 r / min for 120 min under air-tight conditions on a magnetic heating stirrer until PEUR was completely dissolved; polyethylene glycol diacrylate (PEGDA) with a mass ratio of 4:1 to PEUR was weighed and stirred at 30°C and 600 r / min for 30 min to mix the PEGDA and PEUR solutions evenly; the evenly mixed PEGDA-PEUR / DMF solution was placed under an ultraviolet lamp with a power of 20 W and an ultraviolet wavelength of 365 nm for 60 min to obtain a slightly viscous PEUR-cross-linked PEGDA network / DMF polymer solution; 20 wt% of the total weight of the composite solid electrolyte was weighed and added to the polymer solution, and stirred at 30°C and 600 r / min for 30 min to completely dissolve LiTFSI; 25 wt% of the total weight of the composite solid electrolyte was weighed. 6.5 Ln3Z 1.5 Ta 0.5 O 12 (LLZTO) inorganic filler was mixed evenly with 2 mL of DMF solution and then ultrasonicated for 60 min. After ultrasonication, the obtained LLZTO suspension was added to the polymer solution, and stirred for 30 min at 30 ° C and 600 r / min to obtain a solid electrolyte mixture. The solid electrolyte mixture was poured on a glass plate, immersed in anhydrous ethanol for 12 h, taken out after soaking, and dried at 80 ° C under vacuum conditions for 12 h to obtain a composite solid electrolyte.
[0024] Step S2: The composite solid electrolyte obtained in step S1 is cut into solid electrolyte discs with a diameter of 16 mm, and assembled into Li||stainless steel, LFP||Li, NCM811||Li button batteries (CR2032 mold) in a glove box for subsequent testing. Example 2
[0025] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass ratio of polyethylene glycol diacrylate in step S1 is replaced from 4:1 to 1:0.15, the solute salt lithium bistrifluoromethanesulfonyl imide is replaced by lithium hexafluorophosphate, and the filler Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 The weight percentage of 25wt% was replaced by 15wt%, and the solvent DMF was replaced by N-methylpyrrolidone. Example 3
[0026] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass ratio of polyethylene glycol diacrylate in step S1 is replaced from 4:1 to 1:0.05, the solute salt lithium bistrifluoromethanesulfonyl imide is replaced by lithium bis(trifluoromethanesulfonyl imide), and the filler Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 The weight percentage of 25wt% was replaced by 5wt%, and the solvent DMF was replaced by dimethyl sulfoxide. Example 4
[0027] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass ratio of polyethylene glycol diacrylate in step S1 is replaced from 4:1 to 1:0.35, the solute salt lithium bistrifluoromethanesulfonyl imide is replaced by lithium difluorooxalatoborate, and the filler Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 The weight percentage of 25wt% was replaced by 35wt%, and the solvent DMF was replaced by ethylene glycol dimethyl ether. Example 5
[0028] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass ratio of polyethylene glycol diacrylate in step S1 is replaced by 4:1 to 1:0.45, the solvent salt lithium bistrifluoromethanesulfonyl imide is replaced by lithium nitrate, and the filler Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 The weight percentage of 25wt% is replaced by 45wt%.
[0029] Comparative Example 1 Step S1: 2.0 g of polyether polyurethane (PEUR, Yantai Wanhua WHT-8190RV) was weighed and mixed with 8 mL of DMF solvent, and stirred for 120 min at 80 ° C and 600 r / min on a magnetic heating stirrer under air isolation until PEUR was completely dissolved; 20 wt% of lithium bistrifluoromethanesulfonyl imide (LiTFSI) was weighed and added to the polymer solution, and stirred at 30 ° C and 600 r / min for 30 min to completely dissolve LiTFSI; 25 wt% of Li 6.5 Ln3Z 1.5 Ta 0.5 O 12(LLZTO) inorganic filler was mixed evenly with 2 mL of DMF solution and then ultrasonicated for 60 min. After ultrasonication, the obtained LLZTO suspension was added to the polymer solution and stirred at 30 ° C and 600 r / min for 30 min to obtain a solid electrolyte mixture. The solid electrolyte mixture was poured on a glass plate, immersed in anhydrous ethanol for 12 h, taken out after soaking, and dried at 80 ° C under vacuum conditions for 12 h to obtain a composite solid electrolyte.
[0030] Step S2: The composite solid electrolyte obtained in step S1 is cut into solid electrolyte discs with a diameter of 16 mm, and assembled into Li||stainless steel, LFP||Li, NCM811||Li button batteries (CR2032 mold) in a glove box for subsequent testing.
[0031] Comparative Example 2 Step S1: 2.0 g of polyether polyurethane (PEUR, Yantai Wanhua WHT-8190RV) was weighed and mixed with 8 mL of DMF solvent, and stirred for 120 min at 80 ° C and 600 r / min under air-tight conditions on a magnetic heating stirrer until PEUR was completely dissolved, polyvinylidene fluoride (PVDF) with a mass ratio of 4:1 to polyether polyurethane was weighed and added to the above slurry, and continued to heat and stir at 80 ° C to mix evenly, and then 20 wt% of the total weight of the composite solid electrolyte was added. The solute salt lithium trifluoromethylsulfonyl imide was added, and after stirring and mixing evenly, 25 wt% of the total weight of the composite solid electrolyte filler Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 (LLZTO), transferred to a ball mill after stirring, coated on a mold after ball milling and mixing evenly, immersed in anhydrous ethanol solvent to replace the solvent DMF in the slurry, taken out after standing, and dried to obtain a composite solid electrolyte.
[0032] Step S2: The composite solid electrolyte obtained in step S1 is cut into solid electrolyte discs with a diameter of 16 mm, and assembled into Li||stainless steel, LFP||Li, NCM811||Li button batteries (CR2032 mold) in a glove box for subsequent testing.
[0033] Performance Testing 1. Test methods (1) Tensile specimens were prepared from the composite solid electrolytes obtained in Example 1 and Comparative Examples 1 and 2, and the tensile properties were tested.
[0034] (2) A stainless steel||stainless steel symmetric button cell was prepared using the composite solid electrolyte obtained in Example 1 and Comparative Examples 1 and 2, and an electrochemical impedance spectroscopy test was performed to analyze the charge transfer resistance and calculate the ionic conductivity based on the electrolyte thickness and area.
[0035] (3) The Li||Li symmetric button cell prepared by the composite solid electrolyte obtained in Example 1 and Comparative Example 1 was tested at 0.1 mA / cm in the LANDdt test software. 2 Constant current charge and discharge tests were carried out at a current density of .
[0036] (4) The LFP||Li button-type battery prepared by the composite solid electrolyte obtained in Example 1 and Comparative Example 1 was subjected to constant current charge and discharge test at a rate of 2C (1C=170mAh / g) in the LANDdt test.
[0037] 2. Test results like Figure 1 As shown, the composite solid electrolyte obtained in Example 1 has excellent flexibility and good mechanical strength, which helps to obtain good solid-solid interface contact in the battery and reduce the charge transfer resistance at the interface.
[0038] like Figure 2 As shown, the composite solid electrolyte prepared in Example 1 has the smallest bulk resistance, and the ionic conductivity can be calculated according to the following formula:
[0039] in: σ is the ionic conductivity, in mS / cm, L is the material thickness in cm, R b is the bulk resistance, in Ω, S is the contact area in cm 2 The ionic conductivity of Example 1 was calculated to be 1.19 mS / cm, which was significantly higher than that of Comparative Example 1 (0.31 mS / cm).
[0040] like Figure 3 As shown, the Li||Li symmetrical button-type battery assembled with the composite solid electrolyte obtained in Example 1 can be stably cycled for 1400 h without short circuit. The Li||Li symmetrical button-type battery assembled with the composite solid electrolyte obtained in Comparative Example 1 short circuited at about 630 h.
[0041] like Figure 4As shown, the LFP||Li button battery assembled with the composite solid electrolyte obtained in Example 1 can be stably cycled for 200 cycles at a rate of 2C, with a capacity retention rate of 78% and a first-cycle discharge specific capacity of 140.2 mAh / g. The LFP||Li button battery assembled with the composite solid electrolyte obtained in Comparative Example 1 began to have obvious capacity decay after 25 cycles, and the capacity significantly decayed to 50.6 mAh / g after 50 cycles.
[0042] like Figure 5 As shown, the charge and discharge curves of the LFP||Li button battery assembled with the composite solid electrolyte obtained in Example 1 at different rates all have obvious charge and discharge platforms, indicating that the composite solid electrolyte obtained in Example 1 has good ionic conductivity.
[0043] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A thermoplastic polyurethane elastomer flexible composite solid electrolyte, characterized in that The thermoplastic polyurethane elastomer flexible composite solid electrolyte is prepared from the following raw materials in percentage by weight: 1 wt% to 30 wt% of a solute salt, wherein the solute salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluoroborate, lithium difluorooxalatoborate, lithium nitrate or lithium tetrafluoroborate; 5wt% to 50wt% of an inorganic filler, wherein the inorganic filler is one or more of an active filler or an inert filler, the active filler is one or more of a garnet filler, a perovskite material, a LISICON filler or a NASICON filler, and the inert filler is one or more of natural clay, SiO2 or Al2O3; The polymer matrix is 40wt% to 90wt%, and the polymer matrix is composed of a polymer A and a compound B in a mass ratio of 1:1 to 20, wherein the polymer A is one or more of polyether polyurethane, polyester polyurethane, polyimide polyurethane or polyurea polyurethane, and the compound B is one or more of polyethylene glycol diacrylate (PEGDA), pentaerythritol triacrylate (PPETA) or pentaerythritol tetraacrylate (PETA).
2. The thermoplastic polyurethane elastomer flexible composite solid electrolyte according to claim 1, characterized in that The thermoplastic polyurethane elastomer flexible composite solid electrolyte is prepared from the following raw materials in the following weight percentage ratio: 20wt%-30wt% of solute salt, 5wt%-35wt% of inorganic filler, and the balance is a polymer matrix.
3. The thermoplastic polyurethane elastomer flexible composite solid electrolyte according to claim 1, characterized in that: The garnet filler is Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 or Li 7-x Ln3Z 2-x (Nb+Ta) x O 12 One or more of; the perovskite filler is Li 3x La 2 / 3-x TiO3 (LLTO); NASICON type filler is Li 1+x AlxTi 2-x (PO4)3 (LATP) or Li 1+x Al x Ge 2-x (PO4)3(LAGP) or more.
4. The thermoplastic polyurethane elastomer flexible composite solid electrolyte according to claim 1, characterized in that: The mass ratio of polymer A to compound B in the polymer matrix is 1:2-5.
5. A method for preparing the thermoplastic polyurethane elastomer flexible composite solid electrolyte according to any one of claims 1 to 4, characterized in that The specific steps are: Step S1: dispersing polymer A in solvent C and heating and stirring until dissolved to obtain a precursor solution; Step S2: adding compound B to the precursor solution obtained in step S1 and stirring to mix evenly; Step S3: placing the mixed solution obtained in step S3 under an ultraviolet lamp for 30 to 120 minutes; Step S4: adding a solute salt to the mixed solution obtained in step S4 and stirring to mix uniformly; Step S5: uniformly dispersing the inorganic filler in the solvent C to obtain a suspension; Step S6: Add the suspension obtained in step S5 to the mixed solution obtained in step S4 and stir to mix evenly to obtain a solid electrolyte mixed solution, then evenly apply the solid electrolyte mixed solution on the mold, immerse it in solvent D to form it, take it out after immersion and vacuum dry it to obtain a thermoplastic polyurethane elastomer flexible composite solid electrolyte, which has good compatibility with lithium metal and also has excellent ion transmission ability.
6. The method for preparing the thermoplastic polyurethane elastomer flexible composite solid electrolyte according to claim 5, characterized in that: The solvent C in step S1 and step S5 is one or more of ethylene glycol dimethyl ether, N-methylpyrrolidone, dimethyl sulfoxide or N,N-dimethylformamide; the solvent D in step S6 is one or more of anhydrous ethanol or acetone.
7. The method for preparing the thermoplastic polyurethane elastomer flexible composite solid electrolyte according to claim 5, characterized in that: In step S3, the power of the ultraviolet lamp is 20W, and the wavelength of the emitted ultraviolet light is 365nm.
8. The method for preparing the thermoplastic polyurethane elastomer flexible composite solid electrolyte according to claim 5, characterized in that: The stirring and mixing in step S1, step S2, step S4 and step S6 are all carried out on a magnetic heating stirrer, and the heating and stirring temperature in step S1 is 60-90°C.
9. A lithium metal battery, characterized in that: A button battery is assembled using the flexible composite solid electrolyte described in any one of claims 1 to 4, a lithium iron phosphate or nickel cobalt manganese 811 positive electrode and a lithium metal negative electrode.
Citation Information
Patent Citations
Flexible composite solid electrolyte and preparation and application thereof
CN117855582A
Cited By
Molecular network modified composite solid electrolyte as well as preparation method and application thereof
CN120809930A
Composite solid electrolyte of thermosetting sodium metal battery as well as preparation method and application of composite solid electrolyte
CN120978188A